Analysis of the application of biomechanics to the prevention of sports injuries in physical education learning - Muhammad Surur (Sriwijaya Journal of Sport, 2023)
The purpose of this study is to examine the connection between using biomechanics to prevent sports injuries in physical education learning, with a sample size of 10 physical education teachers in Muaragembong sub-district, Kabupaten Bekasi. The method used is descriptive quantitative data collection techniques with open semi-structured interviews and questionnaires. Based on the discussion and research data it can be drawn that physical education teachers who have a high level of understanding are strongly related to the prevention of student sports injuries in physical education learning. Based on two factors that influence the relationship, namely, the biomechanics understanding factor obtained a "high" category as many as 8 teachers (80%) and the sports injury prevention factor obtained a "high" category as many as 7 teachers (70%). It is concluded that teachers in the Muaragembong sub-district of Kabupaten Bekasi have a high level of understanding. This statement can be interpreted that the application of biomechanics to the prevention of sports injuries in PE learning has a significant relationship. So that good application in biomechanics will increase the prevention of sports injuries and reduce the number of injuries that occur to students and athletes. So that a good application of biomechanics will increase the prevention of sports injuries and reduce the number of injuries that occur to students and athletes. This will have a positive influence on teachers and students to continue to strive in conducting physical education learning in accordance with the learning objectives.